The Integration of Local Narratives into Character Education at Madrasah Ibtidaiyah - Rosidin; Sumarta; Dinata Firmansyah (Lentera Pendidikan: Jurnal Ilmu Pendidikan dan Keguruan Islam, 2025)
Facing the challenges of globalization, character education in Madrasah Ibtidaiyah (MI) requires an innovative approach to instill strong national and patriotic values. This research addresses the problem of ineffective utilization of rich local culture, such as the tales of Nyi Roro Kidul and Lagaligo, which hold significant potential as contextual learning mediums. Employing a qualitative case study approach, the researchers conducted observations, interviews, and document analysis in several MIs. The findings indicate that the integration of local narratives is effectively implemented through storytelling, dramatization, group discussions, and story-based projects. MI teachers demonstrated innovation by adapting the curriculum, incorporating relevant local narrative elements. This learning approach proved successful in increasing student interest, helping them understand noble local cultural values, and strengthening their local identity. In turn, this reinforced local identity positively impacted their sense of nationhood and nationalism, fostering pride in their history and ancestral heritage. In conclusion, the integration of local narratives is a powerful strategy to enrich character education in MI, create meaningful learning experiences, and simultaneously cultivate local identity while strengthening nationhood and nationalism.